Aperfeiçoamento de um mecanismo sulcador para plantio direto de mandioca - Fey, Emerson (2010)
In the cassava production the conventional tillage, characterized by soil preparation with intensive mobilization, is commonly used. However, when this practice results in the maintenance of small quantities of straw on the soil surface, the erosion becomes imminent, and it is exacerbated by the spacing and slow initial development of this culture, especially until four months after planting. An alternative is the no-tillage system, a type of conservation tillage, in which only the owing/planting furrow is prepared for the deployment of culture, and is widely used in soybean, corn, wheat, beans, and others crops. For cassava, the adoption of this system has raised many questions on the basis of the soil physical properties recommended, according to which the crop requires well-drained and loose soils to allow the proper root development, where the carbohydrates produced by the plant are stored. It is believed that the deployment of a larger soil area in furrow may facilitate the proper development of cassava in no-tillage system and promote the soil protection due the maintenance of straw on the surface. In this context, the objective is improve the furrow opener device of cassava planters using the precepts of the agricultural machinery development process, with the intent of provide the cultivation of cassava in no-tillage system. For the furrow opener development it were implemented the informational, preliminary and detailed design phases of the product development process. It where formulated for the task of preparing the planting furrow, 31 needs of customers who were deployed in 30 customer requirements and then in 27 design requirements. From these requirements and the solutions available on other agricultural machines and implements, the winged tines where selected as a potential solution. So, a layout study where conducted and resulted in the construction of prototypes with different geometries to experimentation with cassava crop and tests of forces. The use of the reference model for the development process of agricultural machinery allowed the development of furrow opener device for the cultivation of cassava in no-tillage system, that have low cost, small number of components, simple manufacturing process and smooth operation. The yield obtained with the cassava crop in conventional tillage and no-tillage was similar, showing that this technique can be used to grow without com